Dampak Keberadaan Transportasi Online (Go-jek) terhadap Penarik Becak dan Ojek Pangkalan - Suherman Arifin (Peradaban: Jurnal Pengabdian Masyarakat, 2025)
Transportation involves the movement of goods or people from one place to another and plays a crucial role in daily human activities. Online motorcycle taxis (ojek online) have become a modern transportation option, using motorized vehicles to fulfill requests for passenger or goods transport efficiently. This study explores the emergence of ojek online services at Serang City train station, an area previously dominated by traditional human-powered rickshaws. The research examines the timeline of their introduction and their socioeconomic impact on traditional rickshaw drivers and base motorcycle taxi drivers. A qualitative descriptive approach was employed, involving direct and indirect interviews, data collection, observation, and in-depth interviews to gather insights. The findings highlight several challenges caused by the operation of ojek online, including reduced income for traditional rickshaw and base motorcycle taxi drivers, the rise of unemployment, increased competition among transportation providers, and heightened traffic congestion around the station. These results emphasize the need for better management of transportation systems to balance modernization and the well-being of affected communities.